1982
DOI: 10.1002/mus.880050811
|View full text |Cite
|
Sign up to set email alerts
|

Motor and sensory neurons of the rat sural nerve: A horseradish peroxidase study

Abstract: Neurons of origin of the rat sural nerve were labelled with horseradish peroxidase. Dorsal root ganglionic cells were located in the L4 and L5 ganglia, and occasionally at the L6 level. Most of these sensory neurons measured under 35 microns in diameter. In keeping with previous electrophysiological studies suggesting the presence of motor fibers to plantar muscles in the rat sural nerve, motoneurons were identified at the caudal end of the L5 spinal segment, intermingled in the posterior aspect of the ventral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 33 publications
2
35
1
Order By: Relevance
“…Janig & McLachlan (1984) and Peyronnard et al (1986 a) have tried this experiment. Both groups have obtained reproducible results from normal material, both in rats and cats, with reasonably consistent matches between the numbers of axons in the nerves and the numbers of labelled cells in the dorsal root and sympathetic ganglia (McLachlan & Janig, 1983;Peyronnard & Charron, 1982;Peyronnard et al 1986a, b;Baron et al 1988). In injured nerves where a stump neuroma had been made to form, however, fewer somata were labelled.…”
Section: Articular Nervesmentioning
confidence: 66%
“…Janig & McLachlan (1984) and Peyronnard et al (1986 a) have tried this experiment. Both groups have obtained reproducible results from normal material, both in rats and cats, with reasonably consistent matches between the numbers of axons in the nerves and the numbers of labelled cells in the dorsal root and sympathetic ganglia (McLachlan & Janig, 1983;Peyronnard & Charron, 1982;Peyronnard et al 1986a, b;Baron et al 1988). In injured nerves where a stump neuroma had been made to form, however, fewer somata were labelled.…”
Section: Articular Nervesmentioning
confidence: 66%
“…After neonatal transection of the sciatic nerve, the sciatic nerve stump and its associated L,-L, dorsal root ganglia and roots (Kaizawa and Takahashi, 1970;Peyronnard and Charron, 1982;Rodin et al, 1983;Wall and Devor, 1981;Wiley and Wall, 1983) were smaller than normal. This is consistent with reports of loss of sensory cell bodies in dorsal root ganglia after nerve injury in young mammals (Aldskogius and Risling, 198 1, 1983;Jorgensen and Dyck, 1979;Ranson, 1906;Risling et al, 1983;Yip and Johnson, 1984) and with the proposition that the patterns of cortical change after neonatal sciatic injury involve alterations in the capacity of the injured nerve to support normal development of the ascending hindpaw projection system.…”
Section: Present Jindingsmentioning
confidence: 97%
“…In our experimental model, the sural nerve was used as the donor, which seems to be very suitable for studying the sprouting specifically of myelinated sensory axons, because > 93% of its myelinated axons are sensory. 58,59 Several observations discussed in detail in our previous papers 11,57,60 demonstrated that in our experimental model the axons in the recipient nerve were axon sprouts (either collateral from uninjured axons or regenerative from injured axons) from the donor nerve, and ruled out the possibility of inadvertent invasion of the regenerating axons from some other source, for example, from the proximal nerve stumps of the transected adjacent peroneal and tibial nerves.…”
Section: Discussionmentioning
confidence: 58%